Fatima mernissi and her methodology in dealing with misogyny hadith: A critical review - Mohd Noor A.Y.; Ab Rahman Z.; Salleh A.D.; Mohd Kashim M.I.A.; Mohd Mokhtar A. (Innovare Academics Sciences Pvt. Ltd, 2024)
Fatima Mernissi is considered as one of the prominent western thinkers and scholars in contemporary Orientalists world. She has produced a numerous intellectual sources comprehensively, especially in the Hadith perspective, had raised and lift up the women position and dignity in Islam. This article aims to investigate the world feminist's point of views from Morocco, Fatima Mernissi where she had made a criticism upon the Hadith with claiming that the Hadith had a discrimination to the position, role and leadership of women in Islam. This was investigated from her ideas and broad understanding of its principle and underlying purposes. The essential understanding of the principle of prophetic hadith was analytically discussed in her writings. The finding shows that the criticism on the Prophetic Hadith has been made due to her historical background whereas she get to live with the situation that under estimate to the Muslim women and left her a deep impact inside her life. The article set forth important framework and methodology towards criticizing prophetic tradition, but have been critically by most of prominent Muslim scholars due to contradiction between her methodology and Islamic principle methodology and deflected from usual meanings. 2020 Innovare Academics Sciences Pvt. Ltd. All rights reserved.